Percepatan Penyelesaian Proyek dengan Penambahan Tenaga Kerja Menggunakan Metode Least Cost Analysis - Kumara, I Nyoman Indra; Tapa, I Gede Fery Surya; Indrashwara, Decky Cipta (Jurnal Teknik Sipil dan Teknologi Konstruksi, 2024)
The Denpasar City Police Multipurpose Building project experienced constraints on project implementation delays due to the Eid al-Fitr holiday. This obstacle resulted in a delay in the progress of project realization by 9.346% or 19 days. The planned progress in week 20 is 66.521%, but the realization in the field has only reached 57.175%. The remaining duration of the project work is 76 days. This analysis aims to optimize the cost and duration of the remaining work with the addition of labor using the least cost analysis method, so that the project can be completed on time and the contractor does not get a fine. The analysis uses primary data in the form of observation costs, facility costs, overhead costs and unexpected costs. Then secondary data in the form of contractor unit price analysis, cost budget plan (RAB), and S curve. The data is analyzed starting from the remaining project work, crashing duration, to finding the cost slope in each job, and using the least cost analysis method to get the optimum cost and duration. The results of the analysis state that the project optimization cost after acceleration is Rp 3,077,713,130.90 with the duration of project implementation accelerated from 76 days to 57 days. The acceleration of the project duration will save the project cost of Rp. 18,428,493.93.